Dances with wolves [videorecording (Blu-Ray)] - Costner, Kevin; McDonnell, Mary; Greene, Graham, 1952-; Grant, Rodney A.; Blake, Michael, 1945-2015 (Metro Goldwyn Mayer Home Entertainment, 2010)
Sent to protect a US outpost on the desolate frontier, Lt. John Dunbar finds himself alone in the vast wilderness. Befriending the very people he's sent to protect the outpost from, the Sioux Indians, Dunbar slowly comes to revere those he once feared. But when the encroaching US Army threatens to overrun the Sioux, he is forced to make a choice, one that will forever change his destiny and that of a proud and defiant nation. Extended Cut. Special features included.